(untitled) (Research, Society and Development, 2022)
This article is intended to describe the experience of working together with a health professional with a physical deficiency, and the challenges of joining the nursing team and direct patient care. This is an experience report, based on the experience in leading a nursing team with a member with a physical deficiency. The author coordinated a team of nursing technicians, from which a person with physical handicap, or who became a great personal challenge, part. Dismissal of preconceptions, even if not supported by the sector, special attention was given to professionals, identifying the potential of the professional, respecting their physical limitations, or what contributed to improve their self-esteem and self-confidence. Despite the difficulty of locomotion, the technique assumed direct assistance to hospitalized cardiopathic patients. The construction of this work reinforces and justifies that, even if a deficiency can have a negative impact on a person, it does not prevent them from carrying out a high-quality work that contributes positively to the well-being of two others. Therefore, it is essential that the institutions, especially the hospitals, be prepared to receive them, being accessible and attractive to better accommodate the professionals with deficiency.